Structural and morphological tuning of iron oxide polymorphs by ECR plasma-assisted thermal oxidation. Issue 53 (28th August 2020) - More, Supriya; Raut, Suyog; Premkumar, S.; Bhopale, Somnath; Bhoraskar, Sudha; More, Mahendra; Mathe, Vikas
Abstract : Schematic representation of Plasma-Assisted Thermal Oxidation (PATO)-processed M-Fe and N-Fe films with surface morphologies at optimized oxygen pressures. Abstract : The work presented involves the generation of oxygen plasma species at low pressure utilizing an Electron Cyclotron Resonance (ECR) plasma reactor, and their interactions with micron- and nano-sized iron films (M-Fe and N-Fe film respectively) prepared using ethyl cellulose processed at high temperature. A specially designed radiation heater (RH) was used to raise the surface temperature of the film rapidly, exactly at the film interface, where the plasma species interact with the surface. As a result of the interaction of oxygen plasma species and temperature, iron is oxidized to different polymorphs depending on the operating pressure and hence oxygen gas flow rate. The phase, as well as the morphology of the film was controlled by monitoring the oxygen flow rate using the unique Plasma-Assisted Thermal Oxidation (PATO) process. Different polymorphs, viz., Fe3 O4, γ-Fe2 O3, α-Fe2 O3 and different morphologies, such as polygonal, compact facets, wire-like (1D) nanostructures at the surface were obtained for the films processed using PATO. The selected PATO-processed films were investigated for Field Electron Emission (FEE) properties. The 1D-grown surface of iron oxide obtained from the M-Fe film showed a turn-on field of 3 MV m −1 and emission current of 337 μA cm −2, whereas the pyramidal surface morphology obtained using N-Fe film gives a turn-on field of 3.3 MV m −1 with an emission current of 578 μA cm −2 .